L’essere-posto-a-distanza. Una condizione antropologica ed ermeneutica - De Angelis, Rossana (Rivista Italiana di Filosofia del Linguaggio, 2015)
This article focuses on the main feature of hermeneutical perspective concerning philosophy of language: the notion of distancing, and the instance of articulation as something intimately connected to the very structure of signification. The hermeneutical perspective concern particularly Gadamer and Ricoeur’s philosophies. To highlight these two features we have to determine the peculiarity of human condition, first compared to other animals’ ones, and then the specificity of human language, compared to other forms of communication. According to Virno and Gambarara’s philosophies of language, the linguistic environnement in which humans live is the proper of human condition (Saussure).This allow to speak about world (Heidegger). According to Gadamer and Ricoeur’s hermeneutical philosophy, this peculiarity could be retraced in the textual dimension of language. This linguistic capacity is unique of the humans and implies a very complex social architecture to be formed and understood. In fact, if animals do have a world indeed, humans are the only animals who need a double distancing to create a social world on the basis of a textual, rather than only a verbal, signification structure.